IMPLEMENTASI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (STUDI KASUS DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR) - Mikel Homes; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The title of this research is Implementation of Law Number 6 Year 2014 About Villages (Case Study of Village of Koto Kampar Hulu Subdistrict Kampar Regency) Based on the background found the phenomenon that occurs in the field of services that ddidapatkan by community from the village government is less satisfactory community, accept the aspirations and suggestions from the village community either in terms of activities of the implementation of Village Government, the Community also did not get information from the Village Government about the development undertaken and the activities of the Village Administration. The formulation of the problem in this research is Implementation of Law Number 6 Year 2014 About Villages (Case Study of Village of Tanjung Subdistrict Koto Kampar Hulu Kampar District). The type used in this research is qualitative with descriptive survey technique. The location of this research was conducted in Desa Tanjung Koto Kampar Hulu sub-district, Kampar regency. The informant is Head of Tanjung Village, Secretary of Tanjung Village Head, Head of BPD and community. The results of Implementation of Law No. 6 of 2014 on Villages in the Village of Tanjung Koto Kampar Hulu Subdistrict Kampar District can be seen from the results of research interviews, that the targeted policy is considered not reached because the community is still not satisfied with improving the quality of life of villagers, the government has been sufficient to do the service to the community and it is different from the opinion of the people who receive the service from the village government, All existing rules have not been fully implemented. And the agent of palaksana here is all the tools of the village government and its staff including Dusun, RT, RW and so on, the attitude of the implementing agency has not been detrimental to the community and yet there is a community that is in compliance with the performance and the service it is doing, Communication as a means of providing understanding to the community about the implementation of autonomy in Desa Tanjung, After the implementation of Law Number 6 Year 2014 About the Village has a high social environment and social life that more menjantingkan the community so that mambantu implementation of Law No. 6 of 2014 About the Village.Keywords: Implementation, Law Number 6 Year 2014 About Village